2019
DOI: 10.14710/reaktor.19.3.96-100
|View full text |Cite
|
Sign up to set email alerts
|

Study on Organic Redox Flow Battery Mechanism using TEMPO and FMN-Na Solutions

Abstract: Among numerous energy storage technologies, redox flow battery is one of the promising technologies that can be used to supply reliable continuation of electricity to electricity grids with a scale up to MW or MWh.  In this paper, the process mechanism and optimization of redox flow battery using organic solution such as Riboflavin-5’-phosphate sodium salt dihydrate (FMN-Na) as anolyte and 4-hydroxy-2,2,6,6-tetramethylpiperidin-1-oxyl (TEMPO) as catholyte were investigated. Sodium and chloride ions in salt fee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 14 publications
0
2
0
Order By: Relevance
“…Spotify dikenalkan secara resmi dan aktif dalam jaringan internet di Indonesia pada 30 Maret 2016. Spotify telah sukses meraih pasar di Indonesia ataupun dunia dan menyediakan hiburan musik yang legal yang digunakan secara streaming atau daring (Kusumah et al, 2017). Spotify menawarkan dua model layanan, yaitu gratis (free) dan berbayar (premium).…”
Section: Pendahuluanunclassified
“…Spotify dikenalkan secara resmi dan aktif dalam jaringan internet di Indonesia pada 30 Maret 2016. Spotify telah sukses meraih pasar di Indonesia ataupun dunia dan menyediakan hiburan musik yang legal yang digunakan secara streaming atau daring (Kusumah et al, 2017). Spotify menawarkan dua model layanan, yaitu gratis (free) dan berbayar (premium).…”
Section: Pendahuluanunclassified
“…Previously, several redox flow battery researches have been done in Indonesia (Silitonga et al, 2021;Kumara et al, 2022;Kusumah et al, 2019). In this work, metallic BPP will be evaluated based on the materials widely available in the market.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, the novelty of this study is mainly on the identification of possible spontaneous chemical reaction within anolyte tank as a potential of self-discharging reaction. Other researchers (Thaller, 1974;Rychcik & Skyllas-Kazacos, 1988;Silitonga et al, 2021;Kumara et al, 2022;Kusumah et al, 2019;Hendriana et al, 2020;Rahmana et al, 2009;Chen et al, 2017;Blanc et al, 2010;Wikipedia., 2022;Kim, 2019;Povar et al, 2019;Wagman et al, 1982;Jiang et al, 2016;Di Blasi et al, 2014;Kabtamu et al, 2017;Tang et al, 2014;Liu et al, 2011;Richards et al, 2012) have not identified this spontaneous reaction. Further investigation is needed to mitigate this possible self-discharging reaction in VRFB.…”
Section: Introductionmentioning
confidence: 99%